Hospital‐acquired complications in intensive care unit patients with diabetes: A before‐and‐after study of a conventional versus liberal glucose control protocol. Issue 6 (18th March 2019) - Luethi, Nora; Cioccari, Luca; Eastwood, Glenn; Biesenbach, Peter; Morgan, Rhys; Sprogis, Stephanie; Young, Helen; Peck, Leah; Knee Chong, Christine; Moore, Sandra; Moon, Kylie; Ekinci, Elif I.; et al.
Abstract : Background: Critically ill patients with diabetes mellitus (DM) are at increased risk of in‐hospital complications and the optimal glycemic target for such patients remains unclear. A more liberal approach to glucose control has recently been suggested for patients with DM, but uncertainty remains regarding its impact on complications. Methods: We aimed to test the hypothesis that complications would be more common with a liberal glycemic target in ICU patients with DM. Thus, we compared hospital‐acquired complications in the first 400 critically ill patients with DM included in a sequential before‐and‐after trial of liberal (glucose target: 10‐14 mmol/L) vs conventional (glucose target: 6‐10 mmol/L) glucose control. Results: Of the 400 patients studied, 165 (82.5%) patients in the liberal and 177 (88.5%) in the conventional‐control group were coded for at least one hospital‐acquired complication ( P = 0.09). When comparing clinically relevant complications diagnosed between ICU admission and hospital discharge, we found no difference in the odds for infectious (adjusted odds ratio [aOR] for liberal‐control: 1.15 [95% CI: 0.68‐1.96], P = 0.60), cardiovascular (aOR 1.40 [95% CI: 0.63‐3.12], P = 0.41) or neurological complications (aOR: 1.07 [95% CI: 0.61‐1.86], P = 0.81), acute kidney injury (aOR 0.83 [95% CI: 0.43‐1.58], P = 0.56) or hospital mortality (aOR: 1.09 [95% CI: 0.59‐2.02], P = 0.77) between the liberal and the conventional‐control group. Conclusion: In this prospective before‐and‐after study, liberal glucose control was not associated with an increased risk of hospital‐acquired infectious, cardiovascular, renal or neurological complications in critically ill patients with diabetes.